THE INFLUENCE OF DIGITAL LITERACY AND SOFT SKILLS MASTERY ON THE JOB READINESS OF FINAL YEAR STUDENTS OF THE MANAGEMENT STUDY PROGRAM, SATYAGAMA UNIVERSITY - Rahmatullah Rahmatullah; I Nyoman Suri Adnyana; Didi Sukardi; Murdiyono Murdiyono (Nusantara Hasana Journal, 2024)
The development of digital technology and the increasingly competitive world of work require students to have good work readiness. This study aims to analyze the influence of digital literacy and soft skills mastery on the work readiness of final-year students of the Management Study Program at Satyagama University. The study used a quantitative approach with a survey method. The research sample consisted of 120 final-year students selected using a purposive sampling technique. Data collection was carried out by distributing questionnaires using a Likert scale. The data analysis technique used multiple linear regression with the help of the SPSS application. The results of the study indicate that digital literacy has a positive and significant effect on student work readiness. Mastery of soft skills also has a positive and significant effect on work readiness. Simultaneously, digital literacy and soft skills contribute significantly to improving the work readiness of final-year students of the Management Study Program at Satyagama University. This study confirms that the ability to use digital technology and mastery of interpersonal skills are important factors in facing the demands of the modern world of work.